КОЛОВРАТКИ СЕМЕЙСТВА BRACHIONIDAE EHRENBERG, 1838 ФАУНЫ УЗБЕКИСТАНА: РОДЫ KERATELLA, PLATIAS, PLATIONUS, NOTHOLCA, ANURAEOPSIS - Сапаров, А.Д.; Мирабдуллаев, И.М. (SCIENCE and SOCIETY, 2019)
The article is devoted to the study of the animals-rotifers, that play a great role in the continental water ecosystems. Short descriptions and tables for determination of species of the family Brachionidae of the fauna of Uzbekistan are presented.